A disproportionality analysis of low molecular weight heparin in the overall population and in pregnancy women using the FDA adverse event reporting system (FAERS) database - Xu, Huanying; Xu, Ningning; Wang, Yingju; Zou, Haoxi; Wu, Suzhen (Frontiers in Pharmacology, 2024)
Background: Low molecular weight heparin(LMWH) is extensively utilized as an anticoagulant for the prevention and management of various thrombotic conditions. However, despite the widespread use of LMWH in clinical indications, its adverse events(AEs) have not received substantial attention, and there is a lack of systematic and comprehensive AE studies. This study aims to evaluate AE signals associated with LMWH in the overall population and in pregnancy women from the FDA Adverse Event Reporting System database. Methods: We used the Standardized MedDRA Query to identify pregnancy-related AE reports. Disproportionality analyses were employed to identify LMWH-related AE by calculating the reporting odds ratios(ROR), proportional reporting ratios(PRR), bayesian confidence propagation neural network(BCPNN), and the empirical Bayesian geometric mean(EBGM). Results: For the overall population, the significantly reported adverse signals in SOCs were pregnancy, puerperium, and perinatal conditions, vascular disorders, blood and lymphatic system disorders, and product issues. The five strongest AEs signal of LMWH-related were anti factor X antibody positive(n=6, ROR 506.70, PRR 506.65, IC 8.31, EBGM 317.03), heparin-induced thrombocytopenia test positive(n=19, ROR 263.10, PRR 263.02, IC 7.65, EBGM 200.79), anti factor X activity increased(n=10, ROR 255.93, PRR 255.89, IC 7.62, EBGM 196.61), heparin-induced thrombocytopenia test(n=14, ROR 231.85, PRR 231.80, IC 7.51, EBGM 182.09), and spontaneous heparin-induced thrombocytopenia syndrome(n=3, ROR 230.31, PRR 230.30, IC 7.50, EBGM 181.16). For pregnancy women, the five strongest AEs signals of LMWH-related included sternal fracture(n=3, ROR 243.44, PRR 243.35, IC 6.61, EBGM 97.94), syringe issue(n=12, ROR 97.49, PRR 97.34, IC 5.94, EBGM 61.21), bleeding time prolonged(n=3, ROR 97.38, PRR 97.34, IC 5.94, EBGM 61.21), spinal compression fracture(n=10, ROR 90.24, PRR 90.13, IC 5.87, EBGM 58.30), and injection site haematoma(n=19, ROR 79.23, PRR 79.04, IC 5.74, EBGM 53.47). Additionally, unexpected AEs associated with LMWH in pregnancy women were observed, including premature baby death, placental necrosis, abortion, antiphospholipid syndrome, systolic dysfunction, compartment syndrome, body height decreased, rubella antibody positive, and ultrasound doppler abnormal. Conclusion: This study identified unexpected AE signals of LMWH-relate in pregnancy women. Our study could provide valuable evidence for the clinical practice of LMWH, especially for identifying AEs and ensuring safe usage in pregnancy women.